PGSD Student Internship Program in The Framework of The MBKM Curriculum (Study of Internship Implementation in The Ngada Region, East Nusa Tenggara) - Dhiu, Lusia Florida; Lawe, Yosefina Uge; Qondias, Dimas; Kaka, Philipus Wungo (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research aims to describe: 1) Preparation for internships, 2) Implementation of internships, 3) Evaluation of internships in the PGSD STKIP Citra Bakti Ngada Study Program. 4) Reveal how the internship program can strengthen the competencies of prospective elementary school teachers. This type of research is qualitative research, with a descriptive design, and uses a phenomenological approach. Data collection methods use questionnaires, interviews and observation. The informants for this research were students of PGSD STKIP Citra Bakti Ngada class of 2020, DPM (Internship Supervisor) and tutor teachers. The data analysis method uses interactive analysis by means of data reduction, data presentation and data verification. The results of this research are: 1) Preparation for the internship in the PGSD STKIP Citra Bakti Ngada study program has been carried out well, students have carried out registration procedures in accordance with the provisions, the DPM (internship supervisor) also provides debriefing to students before being sent to partner schools so that students understand and understand the purpose of holding an internship program. 2) The implementation of the internship program for students of the PGSD STKIP Citra Bakti Ngada study program class of 2020 is in accordance with the guidelines in the internship handbook. 3) Partner elementary schools and DPM provide a joint evaluation at the end of the program 4) Implementation of an internship program for students of the PGSD STKIP Citra Bakti Ngada study program can strengthen the competency of prospective elementary school teachers because, judging from the SKGP (competency standards for novice teachers), it turns out that the competency of novice teachers is also possessed and found in students participating in the internship program as prospective teachers when carrying out the internship program at partner elementary schools. From the results of the research conducted, it can be concluded that the internship program carried out by PGSD STKIP Citr Bakti Ngada study program students runs in accordance with procedures and guidebooks. This internship program can also strengthen the competency of prospective elementary school teachers.